The Effect of Profitability and Capital Structure on Firm Value with Dividend Policy as an Intervening Variable in Textile and Garment Companies in 2023-2024 on the Indonesia Stock Exchange (IDX) - Amelia, Lia; Sunarya, Erry; Danial, R. Deni Muhammad (Universitas Muhammadiyah Pontianak, 2025)
This study aims to analyze the effect of profitability and capital structure on firm value with dividend policy as an intervening variable in textile and garment companies listed on the Indonesia Stock Exchange (IDX) during the period 2023-2024. The research approach used is quantitative with associative research type. The research sample consisted of 16 companies selected by purposive sampling method, with a total of 128 observation data for 8 quarters. The data used is secondary data in the form of financial reports downloaded from the official IDX website. Data analysis was carried out using descriptive statistical techniques and Partial Least Square (PLS) with the help of SmartPLS software. The results showed that profitability (ROA) has no significant effect on firm value (PBV) or dividend policy (DPR). Capital structure (DER) has a negative and significant effect on firm value (PBV), but has no significant effect on dividend policy (DPR). In addition, dividend policy (DPR) also has no significant effect on firm value (PBV) and is unable to mediate the effect of profitability and capital structure on firm value. These findings indicate that in the conditions of the Indonesian textile and garment industry in 2023-2024, profitability and dividend policy factors have not been able to increase firm value directly or indirectly, while too high a capital structure actually reduces firm value in the eyes of investors.